(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics and evaluate the treatment outcomes of breast abscesses at Surgical Department B, K Hospital. Methods: A retrospective descriptive study on 215 patients with breast abscesses who were successfully treated. Results: Breast abscesses commonly occur in young women of childbearing age (average 27.9 years), with 24.2% of cases related to pregnancy and 40.5% to breastfeeding. The majority had a history of breast disease (54.4%) and abscesses larger than 5 cm (61.9%). Before hospitalization, 94.4% had used antibiotics, and 50.7% had undergone incision and drainage. Treatment primarily involved extensive surgical debridement (84.7%), while 15.3% required only incision and drainage. Staphylococcus aureus was the most frequently isolated bacteria (91.5%). The cure rate was 91.6%, with no recorded complications. Conclusion:Breast abscesses are severe infections caused by bacteria, primarily Staphylococcus aureus. Effective treatment ensures a high cure rate (91.6%) with no complications observed during six months of follow-up.